Rachel in the world : a memoir - Bernstein, Jane, 1949- (University of Illinois Press, 2007)
What happens when love is no longer enough? Jane Bernstein thought that learning to accept her daughters disabilities meant her struggles were over. But as Rachel grew up and needed more than a parents devotion, both mother and daughter were confronted with formidable obstacles. Rachel in the World, which begins in Rachels fifth year and ends when she turns twenty two, tells of their barriers and successes with the same honesty and humor that made Loving Rachel, Bernsteins first memoir, a classic. Bernstein's linked narratives center on family issues, social services, experiences with caregivers, and Rachel herself--difficult, charming, hard to fathom, eager for her own independence. Bernstein invites the reader to share the frustrations and unexpected pleasures of finding a place for her daughter, first in her family, and then in the world.
Keywords: Bernstein, Jane, -- 1949-; Glynn, Rachel.; Glynn, Rachel; Parents of children with disabilities -- United States -- Biography.; Parents of children with disabilities -- Psychology.; Youth with disabilities -- United States -- Biography.; Children with disabilities.; People with disabilities.; Parent and child.; Children with Disabilities.; Disabled Persons; Parent-Child Relations; Parents d'enfants handicapés -- États-Unis -- Biographies.; Parents d'enfants handicapés -- Psychologie.; Jeunes handicapés -- États-Unis -- Biographies.; Enfants handicapés.; Personnes handicapées.; Parents et enfants.; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists.; POLITICAL SCIENCE -- Public Policy -- Social Security.; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare.; SOCIAL SCIENCE -- Sociology -- Marriage & Family.; Parents of children with disabilities; Parents of children with disabilities -- Psychology; Youth with disabilities; United States; Electronic resource.; Biographies